1979
DOI: 10.1007/bf00846564
|View full text |Cite
|
Sign up to set email alerts
|

The structured interview and questionnaire methods of assessing coronary-prone behavior in male and female college students

Abstract: Several self-report measures of type A behavior were compared with the Rosenman and Friedman structured interview method of assessment in male and female college students. The student version of the Jenkins Activity Survey was found to correlate relatively weakly with the interview for both males and females, while scales derived from the Gough and Thurstone inventories showed moderate correlations with interview typing for both sexes. A brief scale derived from a recent reanalysis of the Framingham study corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…However, after therapy, the group treated with beta-blocking agents exhibited less Type A behavior than patients in the control group treated with diuretics. This effect was most pronounced in the first three stylistics which contribute most of the global Type A score, and are higly correlated with the Type A score (30). A similar result is reported for monkeys in which animals treated with beta blockers became less aggressive, less anxious, and increased positive social contacts [31).…”
Section: Resultssupporting
confidence: 71%
“…However, after therapy, the group treated with beta-blocking agents exhibited less Type A behavior than patients in the control group treated with diuretics. This effect was most pronounced in the first three stylistics which contribute most of the global Type A score, and are higly correlated with the Type A score (30). A similar result is reported for monkeys in which animals treated with beta blockers became less aggressive, less anxious, and increased positive social contacts [31).…”
Section: Resultssupporting
confidence: 71%
“…The five point scale is the same as the Gough scale. McDougal et al (22) found these measures of behavior type to correlate better with the structured interview than the JAS. In the section of results (below) the structured interview assessments will be referred to as Type A SI , the Gough assessments as Type A G , and the Thurstone Activity Survey assessments as Type A T .…”
Section: Psychological Measuresmentioning
confidence: 99%
“…30 The activity subscale of the Thurstone Temperament Schedule has been found to correlate with the structured interview, 31 which is seen as the benchmark for assessment of the type A behavior pattern. [32][33][34] It has also been found to correlate with CHD. 35 It shows a high test-retest correlation over a span of many years and has evidenced the highest test-retest correlation among a variety of TABP self-report questionnaires.…”
Section: Instrumentsmentioning
confidence: 99%